Impact of Uneven Agricultural Business Development on Rural Socio-Economic Dynamics - Belei, Svitlana; Lopatynskyi, Yuri; Petrukha, Nina; Lahodyn, Nazar; Nezhyd, Yuliia (European Journal of Sustainable Development, 2025)
Modern countries pay attention to the significant economic importance of the agricultural sector. The situation remains increasingly severe due to some unfavorable socioeconomic circumstances, as the pandemic and the wars between Russia and Ukraine coincided. Agricultural activities contribute to economic stabilization, while local consumption and food supply for the territory can also occur through agricultural activities. In this regard, the study of asymmetric development of agrarian business is becoming quite relevant since it can prevent its negative impact on the economic and social life of rural areas. The purpose of the academic paper is to develop a theoretical and methodological apparatus for the asymmetric development of agrarian business and analyze the current situation and possible prospects for the development of rural areas in the countries of the European Union. General scientific and specific scientific research methods were used in the research. In particular, the methods of generalization, systematization, analysis of modern scientific sources and comparison were applied. A statistical approach was used to gather the required data and estimate the data on cumulative income shares in order to determine the extent of agricultural land in the research area. The Lorenz curve was constructed using a graphical method. The Gini coefficient was calculated using a mathematical method. The Gini index was used to determine the current level of asymmetry in the development of agribusiness in the European Union countries. The index sums up to a value of G = 0.08, which falls within the range 0 ? G < 0.3; therefore, it can be argued that there is a high and stable level of socio-economic inequality in rural areas of the European Union member states. If such information is properly linked to the general imbalance of changes and the probable food crisis at the moment, then in the EU countries it can be said that the agricultural landscape is relatively stable. Thus, the asymmetry of development concerns agribusiness, which may be uneven in terms of the main production factors necessary for the creation of agricultural products, and production relations exist between all levels of enterprises, within which the conditions differ in terms of the level of development and the scale that exist within the socio-economic territory. The deterioration of the qualitative and quantitative state of infrastructure provision, the increase in the aging of the population – all the outlined bring asymmetric development to high levels as one of the negative socio-economic factors. Thus, the members of the European Union introduce systemic financial measures for periodic financing of priority areas of agribusiness and infrastructure solutions to improve logistics for rural areas, which reflect very unequal levels of rural inequality in different EU Member States. Keywords: agribusiness, productivity, agricultural production, rural settlements, productivity